Mettre en scène Bérénice : pour en finir avec le palais à volonté - Servane L’Hopital (Etudes Epistémè)
It is invariably difficult to stage Racine – and to find a visual aesthetics capable of measuring up to his use of language – without resorting to aesthetic clichés handed down by tradition. Staging Berenice, in particular, may prove even more difficult due to the simplicity of its plot and its emphasis on “majesty”. How may the “tristesse majestueuse” described in Racine’s foreword be rendered onstage? We are often limited by the traditional idea that space, in Racine, is a “palais à volonté” – an abstract, and not a realistic, place. It is also often said that words and their power, in Racine, are more vital than the notion of space. By studying Berenice and several of its scenic avatars, we attempt on the contrary to show that space in Berenice plays an essential dramaturgical role, both in terms of structure and visual effect. It is within this overdetermined space that Racine’s sublime conception of love is consecrated.